PEMBERDAYAAN KEWIRAUSAHAAN UNTUK ANAK TUNARUNGU DENGAN PEMBUATAN SELAI NANAS - Misnawati Misnawati; Abdul Aziz; Anwarsani Anwarsani; Siti Rahmawati; Petrus Poerwadi; Nirena Ade Christy; Ibnu Yustiya Ramadhan; Yulina Mingvianita; Stefani Ratu Lestariningtyas; Syarah Veniaty (Bajang Institute, 2022)
One of the aspirations that partners want is for deaf children to have an entrepreneurial spirit. Entrepreneurs have an important role in permeating business activities with an entrepreneurial spirit and turning that spirit into energy to engage in reforms, especially in the manufacture of pineapple jam. Deaf children are taught how to process, distribute, and market products. For this reason, through the Intellectual Product Business Development Program the